Trends and differentials in school enrollment in Bangladesh villages - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
Based on data from a nationally representative sample survey of children aged 6-15, the author concludes that the enrollment rate has been declining since 1995 particularly among the boys in the rural areas of Bangladesh. Most children begin their school at age 8. Regional variation in enrollment is very wide. Dropout rate has remained high particularly at the lower grades. ~early half of the students are enrolled in non-government institutions. The enrollment can be raised further if the education program provides special emphasis on younger children, low-enrolled communities and the children of illiterate parents.